2020
DOI: 10.1177/1932202x20929963
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Instruments for Measuring Affective Outcomes in Gifted Education

Abstract: With increasing attention to examining cognitive strengths and achievements related to social and emotional variables, it is imperative that instruments developed and used to assess change be valid and reliable for measuring underlying constructs. This study examines instruments identified and/or developed to measure four noncognitive constructs (i.e., student engagement, self-efficacy, growth mindset, and stereotype threat) as outcome variables in a study with elementary-aged students in high-poverty rural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In addition to the studies conducted by Sarouphim and Maker (and her colleagues) were a series of individual validation studies conducted by a number of different scholars. These included studies to demonstrate (a) the validity of the HOPE scale in the independent assessment of academic giftedness and social giftedness among low-income rural and urban students (Peters & Gentry, 2010); (b) the validity of instruments that measure four noncognitive constructs (i.e., student engagement, self-efficacy, growth mindset, and stereotype threat) relating to the language arts in a low-income rural community (Callahan et al, 2020); (c) the effectiveness of an expanded above-level testing model (involving a broadly defined group of high achieving students) to identify rural gifted students for an extracurricular STEM enrichment program (Assouline et al, 2017); and (d) the psychometric properties of the My Class Activities instrument in the assessment of student attitudes toward their class activities with respect to interest, challenge, choice, and enjoyment (Gentry et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the studies conducted by Sarouphim and Maker (and her colleagues) were a series of individual validation studies conducted by a number of different scholars. These included studies to demonstrate (a) the validity of the HOPE scale in the independent assessment of academic giftedness and social giftedness among low-income rural and urban students (Peters & Gentry, 2010); (b) the validity of instruments that measure four noncognitive constructs (i.e., student engagement, self-efficacy, growth mindset, and stereotype threat) relating to the language arts in a low-income rural community (Callahan et al, 2020); (c) the effectiveness of an expanded above-level testing model (involving a broadly defined group of high achieving students) to identify rural gifted students for an extracurricular STEM enrichment program (Assouline et al, 2017); and (d) the psychometric properties of the My Class Activities instrument in the assessment of student attitudes toward their class activities with respect to interest, challenge, choice, and enjoyment (Gentry et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies have been conducted on the topic of motivation with rural gifted students. One study that investigated multiple different forms of motivation among rural gifted students is Callahan et al (2020), which validated instruments designed to assess the constructs of student engagement, self-efficacy, growth mindset, and stereotype threat with respect to the language arts with gifted elementary school students in a high poverty rural community. After pilot testing, and consultation with relevant experts in language arts and gifted education, the study produced a revised and redeveloped set of instruments with sound psychometric properties.…”
Section: Resultsmentioning
confidence: 99%
“…The Engagement versus Disaffection Scale (EvsD; Skinner et al, 2009) has been effective for assessing and monitoring behavioral engagement of gifted students (Callahan et al, 2020). This same measure (the survey portion of the EvsD) was implemented as part of the ECLS-K study with gifted students, as well as those with learning disabilities and dual exceptionalities.…”
Section: Behavioral Engagement Considerations For Students With Disab...mentioning
confidence: 99%
“…In one study of the effectiveness of two commercially available explicit instruction approaches used to address the LRP needs of 49 sixth, seventh, and eighth graders living in rural areas, Shippen et al (2014) found that students with more skills at pretest demonstrated more growth at posttest, underscoring the importance of paying attention to the initial capabilities of students when evaluating program effectiveness. Additionally, intervention placement procedures must be carefully implemented due to underlying factors that may not parallel placement practices in other places (Callahan et al, 2020). Lastly, in an effort to resist polarizing and rigid conceptions common to socially, culturally, and economically marginalized spaces (Peine et al, 2020), literacy improvement efforts must engage in a partnership and strengths-based approach (Knight et al, 2016).…”
Section: Rural Contextual Factorsmentioning
confidence: 99%